A study into the need for legal measures against blogging in Malaysia / Siti Nursarah Saroni, Sofia Shereen Kambali, Syahrulfaizi Adli Md Desa - Saroni, Siti Nursarah; Kambali, Sofia Shereen; Md Desa, Syahrulfaizi Adli (2007)
In Malaysia, the Internet has become an essential part of the citizen daily life. It can be said that offices in Malaysia are connected to the Internet. The Internet is originated from the United States which was developed in 1962 by the United States Defence Advanced Research Projects Agency (DARPA).1 This was called the Intemeting project and the system of networks, which emerged from the research, later it was known as the "Internet" Malaysia has launched its Multimedia Super Corridor3 project (hereinafter as MSC) by the former Prime Minister Tun Mahathir Mohamed in 1999. The objective of this launching is to attract investment from the software firms, electronic publishers, telecommunication specialists and other multimedia ventures⁴ The Malaysian had a chance to experience the unlimited access of information better and the Internet had become a medium to communicate by the introductionof Internet. The usage of Internet by household in Malaysia is shown in a survey published by the Malaysian Communications and Multimedia Commission (MCMC) which was conducted in 2005. Its aim is to address user side data gaps on attributes and current trends on the use of Internet in Malaysian homes. The finding of the survey shows the age group of '15-19' has the highest number accounting for 18.6 percent of all Internet users in private households.5 In addition to that, with respect to the intensity of usage, Malaysian surfers tend to surf 9 hours per week. The survey done had shown that the Malaysian are beginning to be more computer literate and are more dependent on the internet for information.